Unity character animation with Mecanim : a detailed guide to the complex new animation tools in Unity, packed with clear instructions and illustrated with original content in the context of a next generation zombie apocalypse adventure game /: a detailed guide to the complex new animation tools in Unity, packed with clear instructions and illustrated with original content in the context of a next generation zombie apocalypse adventure game. (2014) - Dean, Jamie
No abstract available